Optimal Embryo Selection: The Irreplaceable Role of the Embryologist in an Age of Advancing Technology - Lauren Kendall Rauchfuss; Yulian Zhao; David Walker; Terri Galantis; Jolene Fredrickson; Kathrynne Barud; Chandra Shenoy (Journal of Human Reproductive Sciences)
Background: Time-lapse incubators allow for ongoing evaluation of embryos without culture condition disruption. The use of time-lapse incubation has been shown to improve outcomes either by improving overall conditions or providing additional information to aid in embryo selection for transfer. Time-lapse incubators can also utilise morphokinetic models to rank embryos based on morphokinetic parameters. We sought to compare a morphokinetic model for embryo comparison to traditional morphologic evaluation. Aims: The aim of the study is to compare a morphokinetic model for embryo comparison to traditional morphologic evaluation. Settings and Design: This is a retrospective cohort design. Materials and Methods: Embryos cultured in a time-lapse culture system that had traditional morphologic evaluation, morphokinetic modelling and known live birth outcomes were included in this study. Embryos with unknown competence were excluded, including when two embryos were transferred with a single live birth resulted. Statistical Analysis Used: Receiver operating characteristic (ROC) curves were determined for both the morphologic analysis and the morphokinetic model on culture day 3 and day 5. Using the ROC-determined cutoff that optimised both sensitivity and specificity, a binary outcome for each test was analysed using agreement statistics to determine if one method of embryo evaluation was superior to the other. Results: Morphological and morphokinetic grading were both predictive of embryo competence on days 3 and 5. However, on day 3, morphologic grading was superior to morphokinetic grading with area under the curve (AUC) of 0.66 (P < 0.001) and 0.58 (P = 0.009), respectively. Contrarily, on day 5, the morphokinetic model had a higher AUC of 0.65 (P = 0.03) compared to the morphologic grading, AUC 0.56 (P = 0.02). Conclusion: Traditional morphology was noted to be a better diagnostic tool (higher AUC) on culture day 3 while a morphokinetic model was superior on day 5.